Molybdenum disulfide nanosheet modified urea formaldehyde / melamine resin as well as preparation and application thereof

Through hydrothermal synthesis and surface functional group modification technology, modified urea formaldehyde/melamine resin was prepared, which solved the problem of fast curing speed and low compressive strength of existing resin sand-sand solidifying agents at high temperatures, achieved higher temperature resistance and compressive strength, and significantly improved the sand-solidization effect and permeability retention rate.

CN119684614AActive Publication Date: 2025-03-25PETROCHINA CO LTD

Patent Information

Application Number
CN202311230204.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The existing resin sand solidifiers have problems such as too fast curing speed, low compressive strength, poor tolerance to formation fluids and low permeability retention at high temperatures, which are difficult to meet the needs of medium and high liquid yields in petroleum mining.

Method used

Molybdenum disulfide nanosheets were prepared by hydrothermal synthesis, and the surface functional group modification and copolymerization reaction were carried out by copolymerization of aldehydes and polyamine compounds with the modified molybdenum disulfide nanosheets to form a modified urea formaldehyde/melamine resin, which increased its stability and compressive strength at high temperatures.

Benefits of technology

The temperature resistance and compressive strength of the resin are improved, the dispersion of nanosheets in the resin is improved, the binding ability with sand and gravel is enhanced, and the sand solidification effect and permeability retention rate are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684614A_ABST
    Figure CN119684614A_ABST
Patent Text Reader

Abstract

The invention discloses molybdenum disulfide nanosheet modified urea formaldehyde / melamine resin as well as preparation and application thereof. A preparation method of the molybdenum disulfide nanosheet modified urea formaldehyde / melamine resin comprises the following steps: (1) preparing molybdenum disulfide nanosheets from a sulfur source and a molybdenum source by adopting a hydrothermal synthesis method; (2) carrying out surface functional group modification on the molybdenum disulfide nanosheet by using a surface functional group modifier; (3) carrying out copolymerization reaction on aldehydes, a compound containing polyamido and the molybdenum disulfide nanosheet modified by the surface functional group in the step (2) to obtain molybdenum disulfide nanosheet urea formaldehyde / melamine resin; and (4) modifying the molybdenum disulfide nanosheet urea formaldehyde / melamine resin by using a silane coupling agent to obtain the molybdenum disulfide nanosheet modified urea formaldehyde / melamine resin. According to the method disclosed by the invention, the polymer is copolymerized and grafted onto the molybdenum disulfide nanosheet, so that the problems that urea formaldehyde / melamine resin is insufficient in temperature resistance and poor in pressure resistance after being solidified with a rock core are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin and the preparation and application thereof. Background Art

[0002] About 70% of the world's oil resources are located in poorly consolidated reservoirs. These reservoirs are usually relatively young in geological age. Since they have not been cemented together by mineral deposition in natural processes, many reservoirs are prone to sand production. Sand production is particularly evident in cases of changing ground stress, high oil production rates, pore collapse and formation water. Sand production brings high costs and many troubles to the oil industry. For example, it may cause damage to downhole and surface equipment, resulting in serious safety problems including blowouts and shutdowns; sand production also reduces the oil production of production wells, which requires more wells to achieve a stable total production, resulting in increased costs.

[0003] Various sand consolidation methods are used at oil production sites to reduce sand production during the production process, such as filling the formation with resin-coated granular solids and bonding loose sand with resin. Resin-bonded loose sand has the advantages of short well site preparation time and low injection pressure. Currently, the resins commonly used in sand consolidation technology include epoxy resin, polyester resin, phenolic resin, urea-formaldehyde resin, furan resin, etc. However, the resins currently used have the following defects at high temperatures: (1) The curing speed is too fast and the resins are cured before being injected into the formation; (2) The compressive strength is low and cannot meet the demand for sand consolidation when the liquid production is high; (3) The tolerance to formation fluid is poor; (4) The permeability retention rate is low.

[0004] Studies have shown that when nanomaterials are added to the resin sand consolidator, the nanomaterials and the resin sand consolidator participate in the curing reaction together, thereby improving the heat resistance of the resin sand consolidator. However, nanomaterials are not easy to disperse in polymers, and may even accelerate the agglomeration of nanomaterials. At the same time, due to the van der Waals force between nanomaterials and polymers, chromatographic separation will occur at high temperatures, causing the nanomaterials to agglomerate. Summary of the invention

[0005] The present invention is made in order to improve the heat resistance and thermodynamic properties of urea-formaldehyde / melamine resin while improving the dispersibility of molybdenum disulfide nanosheets in urea-formaldehyde / melamine resin.

[0006] As a first aspect of the present invention, it relates to a method for preparing a urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets, comprising the following steps:

[0007] (1) preparing molybdenum disulfide nanosheets from a sulfur source and a molybdenum source by a hydrothermal synthesis method;

[0008] (2) modifying the surface functional groups of the molybdenum disulfide nanosheets using a surface functional group modifier;

[0009] (3) copolymerizing aldehydes, polyamine-containing compounds and the molybdenum disulfide nanosheets modified with surface functional groups in step (2) to obtain molybdenum disulfide nanosheet urea-formaldehyde / melamine resin;

[0010] (4) Using a silane coupling agent to modify the molybdenum disulfide nanosheet urea-formaldehyde / melamine resin to obtain a molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

[0011] In one or some optional embodiments, the step (1) specifically includes:

[0012] A molybdenum source and a sulfur source in a molar ratio of 1:5 to 1:15 are added to a 30% isopropanol aqueous solution and stirred for 10 to 20 minutes; the mixed solution is then subjected to a hydrothermal reaction at 160 to 200° C. for 12 to 24 hours; the product after the hydrothermal reaction is washed with deionized water to obtain molybdenum disulfide nanosheets.

[0013] In one or some optional embodiments, the molybdenum source includes one or a combination of two or more of molybdenum trioxide, molybdenum pentachloride and sodium molybdate; more preferably, the molybdenum source is molybdenum trioxide.

[0014] In one or some optional embodiments, the sulfur source includes one or a combination of two or more of thiourea, potassium thiocyanate, potassium sulfide and thioformamide.

[0015] In one or some preferred embodiments, the temperature of the hydrothermal reaction is 180° C. and the reaction time is 20 h.

[0016] In one or some optional embodiments, the step (2) specifically includes:

[0017] Molybdenum disulfide nanosheets and a surface modification functional group agent are added to deionized water, stirred for reaction, and then the reaction product is washed with deionized water to remove unreacted surface modification functional group agent, and then dried to obtain molybdenum disulfide nanosheets with surface modification functional groups.

[0018] In one or some optional embodiments, the size of the molybdenum disulfide nanosheets is 100-500 nm, preferably 100-200 nm.

[0019] In one or some optional embodiments, the mass ratio of the molybdenum disulfide nanosheets to the surface modification functional group agent is 1:1 to 1:10, preferably 1:1.

[0020] In one or some preferred embodiments, the surface modification functional group agent is urea.

[0021] In one or some optional embodiments, the stirring reaction refers to: firstly ultrasonicating at room temperature for 5 to 15 minutes, preferably for 10 minutes; and then stirring the reaction at 60°C for 6 to 12 hours, preferably for 10 hours.

[0022] In one or some optional embodiments, the power of the ultrasound is 10-25 Hz, preferably 19.2 Hz; the rotation speed of the stirring is 500-1500 rpm, preferably 1000 rpm.

[0023] In one or some optional embodiments, the drying temperature is 50-90°C, preferably 50°C.

[0024] In one or some optional embodiments, the step (3) specifically includes the following steps:

[0025] (301) Aldehydes and the first batch of polyamine-containing compounds were added to a four-necked flask, the pH of the solution was adjusted to 8-9.5 with 40% sodium hydroxide solution, and the reaction was carried out at 80-90 °C for 20-45 min;

[0026] (302) adding a second batch of polyamine-containing compounds and the molybdenum disulfide nanosheets with surface-modified functional groups, adjusting the pH value to 4.5-5.5 with 40% formic acid solution, and reacting at 80-90° C. until the system becomes viscous;

[0027] (303) The reaction temperature was lowered to 50–70 °C, the pH value of the solution was adjusted to 7.0–8.5 with 40% sodium hydroxide solution, and a third batch of polyamine-containing compounds was added. The mixture was reacted for 15–30 min and then cooled to room temperature to obtain molybdenum disulfide nanosheet urea-formaldehyde / melamine resin.

[0028] In one or some optional embodiments, the molar ratio of the polyamine-containing compound to the aldehyde is 1:1 to 1:3.

[0029] In one or some optional embodiments, the mass ratio of the aldehydes and the compounds containing polyamine groups to the molybdenum disulfide nanosheets with surface modified functional groups is 200:1 to 10:1, preferably 100:1 to 50:1.

[0030] In one or some optional embodiments, the aldehydes are selected from one or a combination of two of formaldehyde, hexamethylenetetramine and paraformaldehyde.

[0031] In one or some optional embodiments, the compound containing a polyamine group is selected from one or a combination of urea and melamine.

[0032] In one or some optional embodiments, the first batch of polyamine-containing compounds accounts for 30-50% of the total added mass; the second batch of polyamine-containing compounds accounts for 30-40% of the total added mass; and the third batch of polyamine-containing compounds accounts for 10-40% of the total added mass.

[0033] In one or some optional embodiments, the step (4) specifically includes the following steps:

[0034] The molybdenum disulfide nanosheet urea-formaldehyde / melamine resin is dissolved in acetone, and a silane coupling agent is added, and the mixture is reacted at 80-95° C. for 3-5 hours, and then the organic solvent is removed under reduced pressure to obtain the molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

[0035] In one or some optional embodiments, the mass ratio of the molybdenum disulfide nanosheet urea-formaldehyde / melamine resin to the silane coupling agent is 1:5 to 1:30, preferably 1:10 to 1:15.

[0036] In one or some optional embodiments, the silane coupling agent is selected from one or a combination of two or more of γ-diethylenetriaminepropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

[0037] As a second aspect of the present invention, it relates to urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets prepared by the above method.

[0038] As a third aspect of the present invention, it relates to the application of the above-mentioned molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin in oil field sand control.

[0039] The molybdenum disulfide nanosheets prepared in the method provided by the present invention can be made into a 1T morphology by controlling the hydrothermal synthesis temperature and the molybdenum-sulfur ratio, and then the dispersion of the molybdenum disulfide nanosheets in the polymer is improved by functional group modification of the surface of the molybdenum disulfide nanosheets, thereby increasing the stability of the nanosheet material. Urea-formaldehyde / melamine resin is physically adsorbed or chemically adsorbed on the surface of gravel to consolidate multiple gravels together, but the linear chain is curled in the solution and has limited adsorption on the surface of gravel. After the present invention links the urea-formaldehyde / melamine resin to the molybdenum disulfide nanosheet, it is equivalent to having multiple strong adsorption sites on the surface of the nanosheet, so that the ability to bind with the gravel is stronger and the bonding strength is greatly enhanced.

[0040] The preparation method provided by the present invention increases the rigidity of the polymer by grafting the polymer copolymer onto the molybdenum disulfide nanosheet, thereby increasing the temperature resistance of the polymer. In addition, its multi-"grip" structure can increase the compressive strength while maintaining a high permeability retention rate. The preparation method of the present invention effectively solves the problem of insufficient temperature resistance of urea-formaldehyde / melamine resin and poor pressure resistance after consolidation of the core. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Flow chart for preparing urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets;

[0042] Figure 2 This is a SEM image of the molybdenum disulfide nanosheets prepared in Example 1;

[0043] Figure 3 This is a SEM image of the molybdenum disulfide nanosheets prepared in Example 2;

[0044] Figure 4 This is a SEM image of the molybdenum disulfide nanosheets prepared in Comparative Example 4;

[0045] Figure 5 It is the experimental data diagram of permeability retention rate of different embodiments and comparative examples;

[0046] Figure 6 It is a graph showing the compressive strength experimental data of different embodiments and comparative examples;

[0047] Figure 7 This is the infrared spectrum of the urea-formaldehyde resin modified by molybdenum disulfide nanosheets synthesized in Example 1;

[0048] Figure 8 This is the infrared spectrum of the molybdenum disulfide nanosheet modified melamine resin synthesized in Example 2. DETAILED DESCRIPTION

[0049] The following is a detailed description of the embodiments of the present invention: The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters for which specific conditions are not specified in the following embodiments are generally based on conventional conditions.

[0050] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0051] The inventors implemented the relevant technical scheme with reference to the document "Wu Lin, Ouyang Zhaohui, Cao Shuchao, Yi Delian, Qin Xiaorong, Wang Yan. Research on coal tar modified phenolic resin [J]. Chemical Technology, 2005(04):17-19." and found that coal tar modified phenolic resin can improve the heat resistance of phenolic resin, but the activity of polycyclic aromatic hydrocarbons in coal tar is not high and the amount of coal tar added is difficult to control.

[0052] Based on the above, the inventor's expectations were not met, so the present invention was made.

[0053] The embodiments of the present invention refer to Figure 1 The flowchart of preparing molybdenum disulfide nanosheets modified urea-formaldehyde / melamine resin shown in the figure is to prepare molybdenum disulfide nanosheets modified urea-formaldehyde / melamine resin, and the steps are as follows:

[0054] (1) mixing a sulfur source and a molybdenum source and performing a hydrothermal reaction to obtain 1T molybdenum disulfide nanosheets;

[0055] (2) using urea as a surface functional group modifier to modify the surface functional groups of the 1T molybdenum disulfide nanosheets;

[0056] (3) copolymerizing aldehydes, polyamine-containing compounds and the molybdenum disulfide nanosheets modified with surface functional groups in step (2) to obtain molybdenum disulfide nanosheet urea-formaldehyde / melamine resin;

[0057] (4) Using a silane coupling agent to modify the above-mentioned molybdenum disulfide nanosheet urea-formaldehyde / melamine resin to obtain a molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

[0058] Example 1

[0059] In this embodiment, urea-formaldehyde resin modified with molybdenum disulfide nanosheets is prepared, and the steps are as follows:

[0060] (1) 3 g of molybdenum trioxide powder and 7.92 g of thiourea were added to 100 mL of 30% isopropanol solution and stirred for 10 min; then the mixed solution was poured into a hydrothermal reactor and reacted at 180° C. for 20 hours. Then, the mixture was washed with deionized water to obtain molybdenum disulfide nanosheets.

[0061] (2) The synthesized molybdenum disulfide nanosheets and urea were added to deionized water in a mass ratio of 1:1 and ultrasonicated at room temperature for 10 minutes; then stirred at 60°C and 1000 rpm for 10 hours. Then, the unreacted urea was removed by washing with deionized water, and the molybdenum disulfide nanosheets with surface modified functional groups were obtained after drying at 50°C.

[0062] (3) Add 2 g of urea and 7.5 g of formaldehyde to a four-necked flask, adjust the pH value to 9 with 40% sodium hydroxide solution, and react at 90°C for 30 min; add 2 g of urea and 0.25 g of molybdenum disulfide nanosheets with surface modified functional groups to a reactor, adjust the pH value to 4.5 with 40% formic acid solution, and react until the system becomes viscous; cool to 60°C, adjust the pH value to 8 with 40% sodium hydroxide solution, then add 1 g of urea again, react for 15 min, and then cool to room temperature to obtain molybdenum disulfide nanosheet urea-formaldehyde resin.

[0063] (4) 1 g of molybdenum disulfide nanosheet urea-formaldehyde resin was dissolved in acetone, 5 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 85° C. for 5 hours, and then the organic solvent was removed under reduced pressure to obtain a molybdenum disulfide nanosheet modified urea-formaldehyde resin.

[0064] The SEM image of the molybdenum disulfide nanosheet modified urea-formaldehyde resin is shown in Figure 2 As shown by Figure 2 It can be seen that the molybdenum disulfide nanosheets have a uniform and stable morphology, clear boundaries, and present a complete sheet structure. The infrared spectrum of the molybdenum disulfide nanosheet modified urea-formaldehyde resin is shown in Figure 2. Figure 7 As shown, 3405cm -1 It is the stretching vibration peak of -OH; 2952cm -1 is the CH stretching vibration of the methyl group; 1666cm -1 It is the C=O stretching vibration, i.e. the phthalamide I band, 1564 cm -1 It is the phthalamide n band, which originates from the coupling of the in-plane bending vibration of the NH bond and the stretching vibration of some CN bonds; at 1405cm -1 is CH stretching vibration; 1133cm -1 The stretching vibrations of CO and CN of the aliphatic ether bonds in phthalamide II; 1001 cm -1 It is the deformation vibration of CO on hydroxymethyl; 842cm -1 The CO stretching vibration of the methylene ether bond is at 626 cm -1 is the stretching vibration of Mo-S.

[0065] Example 2

[0066] In this embodiment, molybdenum disulfide nanosheets modified melamine resin is prepared, and the steps are as follows:

[0067] (1) 5 g of sodium molybdate and 23.55 g of potassium thiocyanate were added to 100 mL of 30% isopropanol solution and stirred for 10 min; then the mixed solution was poured into a hydrothermal reactor and reacted at 160° C. for 24 hours. Then the mixture was washed with deionized water to obtain molybdenum disulfide nanosheets.

[0068] (2) The synthesized molybdenum disulfide nanosheets and urea were added to deionized water in a mass ratio of 1:4 and ultrasonicated at room temperature for 15 minutes; then stirred at 60°C and 500 rpm for 10 hours. Then, the unreacted urea was removed by washing with deionized water, and the molybdenum disulfide nanosheets with surface modified functional groups were obtained after drying at 60°C.

[0069] (3) 6 g of melamine and 16.67 g of urotropine were added to a four-necked flask, the pH value was adjusted to 8.5 with 40% sodium hydroxide solution, and the mixture was reacted at 85° C. for 45 min; 6 g of melamine and 0.69 g of molybdenum disulfide nanosheets with surface modified functional groups were added to a reactor, the pH value was adjusted to 5 with 40% formic acid solution, and the mixture was reacted until the system became viscous; the temperature was lowered to 50° C., the pH value was adjusted to 8 with 40% sodium hydroxide solution, and then 3 g of urea was added again. The mixture was reacted for 15 min and then cooled to room temperature to obtain molybdenum disulfide nanosheet melamine resin.

[0070] (4) 1 g of molybdenum disulfide nanosheet melamine resin was dissolved in acetone, 15 g of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was added, and the mixture was reacted at 95° C. for 3 hours, and then the organic solvent was removed under reduced pressure to obtain molybdenum disulfide nanosheet modified melamine resin.

[0071] The SEM image of the molybdenum disulfide nanosheet modified melamine resin prepared in this example is as follows: Figure 3 As shown by Figure 3 It can be seen that the molybdenum disulfide nanosheets have a uniform and stable morphology, clear boundaries, and present a complete sheet structure. The infrared spectrum of the molybdenum disulfide nanosheet modified urea-formaldehyde resin is shown in Figure 2. Figure 8 As shown, 3356cm -1 It is the stretching vibration peak of -OH. 2958cm -1 is the CH stretching vibration of the methyl group; 1561cm -1 The 1444 cm -1 The CH bending vibration of methylene; at 1393cm -1 is the stretching vibration of CH; 1202 is the characteristic absorption peak of Si-C; 1133cm -1 The stretching vibrations of CO and CN of the aliphatic ether bonds in phthalamide II; 987 cm -1 It is the deformation vibration of CO on hydroxymethyl; 812cm -1 The peak is the characteristic peak of triazine ring; 626cm -1 is the stretching vibration of Mo-S.

[0072] Example 3

[0073] In this embodiment, urea-formaldehyde / melamine resin modified with molybdenum disulfide nanosheets is prepared, and the steps are as follows:

[0074] (1) 5 g of molybdenum trioxide and 21.18 g of thioformamide were added to 100 mL of 30% isopropanol solution and stirred for 10 min; then the mixed solution was poured into a hydrothermal reactor and reacted at 200° C. for 24 hours. Then, the mixture was washed with deionized water to obtain molybdenum disulfide nanosheets.

[0075] (2) The synthesized molybdenum disulfide nanosheets and urea were added to deionized water in a mass ratio of 1:5, and ultrasonicated for 10 minutes at room temperature, and then stirred for 10 hours at 60°C and 1000 rpm. The unreacted urea was then washed with deionized water and dried at 50°C to obtain molybdenum disulfide nanosheets with surface modified functional groups.

[0076] (3) 5 g of urea and 18.57 g of formaldehyde were added to a four-necked flask, the pH value was adjusted to 9 with a 40% sodium hydroxide solution, and the reaction was carried out at 90° C. for 45 min; 5 g of melamine and 1.119 g of molybdenum disulfide nanosheets with surface modified functional groups were added to a reactor, the pH value was adjusted to 4.5 with a 40% formic acid solution, and the reaction was carried out until the system became viscous; the temperature was lowered to 70° C., the pH value was adjusted to 8 with a 40% sodium hydroxide solution, and then 5 g of urea was added again, the reaction was carried out for 20 min, and then the reaction was cooled to room temperature to obtain a molybdenum disulfide nanosheet urea-formaldehyde / melamine resin.

[0077] (4) 1 g of molybdenum disulfide nanosheet urea-formaldehyde / melamine resin was dissolved in acetone, 10 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 95 °C for 3 hours, and then the organic solvent was removed under reduced pressure to obtain molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

[0078] Comparative Example 1

[0079] This comparative example prepares a modified urea-formaldehyde resin, which is in contrast to Example 1, and the steps are as follows:

[0080] (1) 2 g of urea and 7.5 g of formaldehyde were added to a four-necked flask, the pH value was adjusted to 9 with 40% sodium hydroxide solution, and the reaction was carried out at 90° C. for 30 min.

[0081] (2) Add 2 g of urea into the reactor, adjust the pH to 4.5 with 40% formic acid solution, and react until the system becomes viscous.

[0082] (3) The temperature was lowered to 60° C., and the pH value was adjusted to 8 with a 40% sodium hydroxide solution. Then, 1 g of urea was added again, and the mixture was reacted for 15 min and then cooled to room temperature to obtain a urea-formaldehyde resin.

[0083] (4) The urea-formaldehyde resin was dissolved in acetone, 5 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 85° C. for 5 hours, and then the organic solvent was removed under reduced pressure to obtain a modified urea-formaldehyde resin.

[0084] Comparative Example 2

[0085] This example prepares a modified melamine resin, which is in contrast to Example 2, and the steps are as follows:

[0086] (1) 6 g of melamine and 10.72 g of formaldehyde were added to a four-necked flask, the pH value was adjusted to 8.5 with 40% sodium hydroxide solution, and the mixture was reacted at 85° C. for 45 min.

[0087] (2) 6 g of melamine was added to the reaction kettle, and the pH value was adjusted to 5 with 40% formic acid solution, and the reaction was continued until the system became viscous.

[0088] (3) cooling to 50° C. and adjusting the pH value to 8 with 40% sodium hydroxide solution, then adding 3 g of urea again, reacting for 15 min, and cooling to room temperature to obtain melamine resin.

[0089] (4) 1 g of melamine resin was dissolved in acetone, 15 g of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was added, and the mixture was reacted at 95° C. for 3 hours. The organic solvent was then removed under reduced pressure to obtain a modified melamine resin.

[0090] Comparative Example 3

[0091] This embodiment prepares the modified urea-formaldehyde / melamine resin, and the steps are:

[0092] (1) 5 g of urea and 18.57 g of formaldehyde were added to a four-necked flask, the pH value was adjusted to 9 with 40% sodium hydroxide solution, and the reaction was carried out at 90° C. for 45 min.

[0093] (2) 5 g of melamine was added to a reaction kettle, and the pH value was adjusted to 4.5 with 40% formic acid solution, and the reaction was continued until the system became viscous.

[0094] (3) cooling to 70° C. and adjusting the pH value to 8 with 40% sodium hydroxide solution, then adding 5 g of urea again, reacting for 20 min, and cooling to room temperature to obtain urea-formaldehyde / melamine resin.

[0095] (4) 1 g of urea-formaldehyde / melamine resin was dissolved in acetone, 10 g of γ-aminopropyltriethoxysilane was added, and the mixture was reacted at 95° C. for 3 hours. The organic solvent was then removed under reduced pressure to obtain a modified urea-formaldehyde / melamine resin.

[0096] Comparative Example 4

[0097] 3g of molybdenum trioxide powder and 3g of thiourea were added to 100mL of 30% isopropanol solution and stirred for 10min. The mixed solution was then poured into a hydrothermal reactor and reacted at 180°C for 20 hours. The molybdenum disulfide nanosheets were then washed with deionized water. The SEM image of the nanosheets is shown in Figure 2. Figure 4 As shown, from Figure 4 It can be seen that the method of this comparative example cannot obtain molybdenum disulfide nanosheets with appropriate size and complete structure.

[0098] Test Example 1

[0099] The resins synthesized in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for permeability retention. The experimental method was in accordance with the Chinese petroleum and natural gas industry standard SY / T 6572-2003 Sand control resin performance evaluation method, and the steps were as follows:

[0100] (1) Core preparation before cementation: Quartz sand with a particle size of 0.4-0.8 mm is placed in a stainless steel core tube, and a copper wire mesh is placed on the inner side of the core tube outlet. The sand sample is filled and vibrated to a constant sand surface, and then a small amount of water is added to saturate it, and the other end is sealed with a copper wire mesh.

[0101] (2) Preparation of cemented cores: ① Weigh 150g of quartz sand into a 500mL beaker and soak it in 50mL of pretreatment solution for 20min. ② Weigh 6% of resin and stir with the quartz sand soaked in the above pretreatment solution to mix evenly. ③ Pour the pre-cemented sand into a glass tube with a perforated rubber plug at one end three times. The perforated rubber plug is padded with a copper wire mesh. Vibrate vertically each time until the sand surface is constant, then inject 80mL of sewage to block the plug hole, place in a constant temperature water bath, and cure at 60℃ for 48h. ④ Take out the core and make cores of 2.5cm and 13cm in length.

[0102] (3) Place the sample (including the sample before and after cementation) in the core holder and adjust the ring pressure value to 0.14-0.35MPa. Then pass a 2% KCL aqueous solution through the core to expel the air in the core. After the flow state stabilizes, calculate the permeability of the sample before and after cementation. And calculate according to the formula:

[0103]

[0104] Where: η is the permeability retention rate, %; K1 is the core permeability after consolidation, mD; K0 is the core permeability before consolidation, mD.

[0105] (4) The experimental data of permeability retention rate of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in the figure below. Figure 5 As shown by Figure 5It can be seen that the permeability retention rate of the urea-formaldehyde / melamine resin modified by the molybdenum disulfide nanosheets prepared in Example 1 is 85%, 79% in Example 2, and 81% in Example 3, while that of Comparative Example 1 is 65%, 61% in Comparative Example 2, and 56% in Comparative Example 3. Without the molybdenum disulfide nanosheets as the core of the core-shell structure, the permeability retention rate is generally around 60%. After adding the molybdenum disulfide nanosheets, the permeability retention rate is generally around 80%.

[0106] Test Example 2

[0107] The compressive strength test of the resins synthesized in Examples 1 to 3 and Comparative Examples 1 to 3 is carried out in the following steps:

[0108] (1) Preparation of cemented cores according to the Chinese Petroleum and Natural Gas Industry Standard SY / T 6572-2003 Sand Control Resin Performance Evaluation Method: ① Weigh 150g of quartz sand in a 500mL beaker and soak it in 50mL of pretreatment solution for 20min. ② Weigh 6% of resin and stir and mix evenly with the quartz sand soaked in the above pretreatment solution. ③ Pour the pre-cemented sand into a glass tube with a perforated rubber plug at one end three times. The perforated rubber plug is padded with a copper wire mesh. Vibrate vertically each time until the sand surface is constant, then inject 80mL of sewage to block the rubber plug hole, place it in a constant temperature water bath, and cure it at 60℃ for 48h. ④ Take out the core and make cores of 2.5cm and 13cm in length.

[0109] (2) The compressive strength test was carried out in accordance with the Chinese petroleum and natural gas industry standard SY / T 5276-2000 for the determination of flexural strength, compressive strength and gas permeability of chemical sand control artificial cores.

[0110] (3) The compressive strength experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the compressive strength of the urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets prepared in Example 1 is 9.5MPa, that of Example 2 is 10MPa, that of Example 3 is 9.3MPa, and that of Comparative Example 1 is 4MPa, that of Comparative Example 2 is 4.5MPa, and that of Comparative Example 3 is 4.3MPa. The addition of molybdenum disulfide nanosheets significantly improves the compressive strength of the resin. The urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets has a higher compressive strength and a good sand consolidation effect. However, the strength of the comparative example is very low and cannot effectively consolidate sand.

[0111] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A method for preparing a urea-formaldehyde / melamine resin modified by molybdenum disulfide nanosheets, characterized in that: The following steps are involved: (1) preparing molybdenum disulfide nanosheets from a sulfur source and a molybdenum source by a hydrothermal synthesis method; (2) modifying the surface functional groups of the molybdenum disulfide nanosheets using a surface functional group modifier; (3) copolymerizing aldehydes, polyamine-containing compounds and the molybdenum disulfide nanosheets modified with surface functional groups in step (2) to obtain molybdenum disulfide nanosheet urea-formaldehyde / melamine resin; (4) Using a silane coupling agent to modify the molybdenum disulfide nanosheet urea-formaldehyde / melamine resin to obtain a molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

2. The method according to claim 1, characterized in that The step (1) specifically comprises: A molybdenum source and a sulfur source in a molar ratio of 1:5 to 1:15 are added to a 30% isopropanol aqueous solution and stirred for 10 to 20 minutes; the mixed solution is then subjected to a hydrothermal reaction at 160 to 200° C. for 12 to 24 hours; the product after the hydrothermal reaction is washed with deionized water to obtain molybdenum disulfide nanosheets.

3. The method according to claim 2, characterized in that The molybdenum source includes one or a combination of two or more of molybdenum trioxide, molybdenum pentachloride and sodium molybdate; more preferably, the molybdenum source is molybdenum trioxide.

4. The method according to claim 2, characterized in that The sulfur source includes one or a combination of two or more of thiourea, potassium thiocyanate, potassium sulfide and thioformamide.

5. The method according to claim 2, characterized in that The temperature of the hydrothermal reaction is 180° C. and the reaction time is 20 h.

6. The method according to claim 1, characterized in that The step (2) specifically comprises: Molybdenum disulfide nanosheets and a surface modification functional group agent are added to deionized water, stirred for reaction, and then the reaction product is washed with deionized water to remove unreacted surface modification functional group agent, and then dried to obtain molybdenum disulfide nanosheets with surface modification functional groups.

7. The method according to claim 6, characterized in that The size of the molybdenum disulfide nanosheets is 100-500 nm, preferably 100-200 nm.

8. The method according to claim 6, characterized in that The mass ratio of the molybdenum disulfide nanosheets to the surface modification functional group agent is 1:1 to 1:10, preferably 1:

1.

9. The method according to claim 6, characterized in that The surface modification functional group agent is urea.

10. The method according to claim 6, characterized in that The stirring reaction means: firstly ultrasonicating at room temperature for 5 to 15 minutes, preferably for 10 minutes; and then stirring at 60° C. for 6 to 12 hours, preferably for 10 hours.

11. The method according to claim 10, characterized in that The power of the ultrasound is 10-25 Hz, preferably 19.2 Hz; the rotation speed of the stirring is 500-1500 rpm, preferably 1000 rpm.

12. The method according to claim 6, characterized in that The drying temperature is 50-90°C, preferably 50°C.

13. The method according to claim 1, characterized in that The step (3) specifically comprises the following steps: (301) Aldehydes and the first batch of polyamine-containing compounds were added to a four-necked flask, the pH of the solution was adjusted to 8-9.5 with 40% sodium hydroxide solution, and the reaction was carried out at 80-90 °C for 20-45 min; (302) adding a second batch of polyamine-containing compounds and the molybdenum disulfide nanosheets with surface-modified functional groups, adjusting the pH value to 4.5-5.5 with 40% formic acid solution, and reacting at 80-90° C. until the system becomes viscous; (303) The reaction temperature was lowered to 50–70 °C, the pH value of the solution was adjusted to 7.0–8.5 with 40% sodium hydroxide solution, and a third batch of polyamine-containing compounds was added. The mixture was reacted for 15–30 min and then cooled to room temperature to obtain molybdenum disulfide nanosheet urea-formaldehyde / melamine resin.

14. The method according to claim 13, characterized in that The molar ratio of the polyamine-containing compound to the aldehydes is 1:1 to 1:

3.

15. The method according to claim 13, characterized in that The mass ratio of the aldehydes and the compound containing polyamine groups to the molybdenum disulfide nanosheets with surface modified functional groups is 200:1 to 10:1, preferably 100:1 to 50:

1.

16. The method according to claim 13, characterized in that The aldehydes are selected from one or a combination of two of formaldehyde, hexamethylenetetramine and paraformaldehyde.

17. The method according to claim 13, characterized in that The compound containing polyamine groups is selected from one or a combination of urea and melamine.

18. The method according to claim 13, characterized in that The first batch of polyamine-containing compounds accounts for 30-50% of the total added mass; the second batch of polyamine-containing compounds accounts for 30-40% of the total added mass; and the third batch of polyamine-containing compounds accounts for 10-40% of the total added mass.

19. The method according to claim 1, wherein: The step (4) specifically comprises the following steps: The molybdenum disulfide nanosheet urea-formaldehyde / melamine resin is dissolved in acetone, and a silane coupling agent is added, and the mixture is reacted at 80-95° C. for 3-5 hours, and then the organic solvent is removed under reduced pressure to obtain the molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin.

20. The method of claim 19, wherein: The mass ratio of the molybdenum disulfide nanosheet urea-formaldehyde / melamine resin to the silane coupling agent is 1:5 to 1:30, preferably 1:10 to 1:

15.

21. The method of claim 19, wherein: The silane coupling agent is selected from one or a combination of two or more of γ-diethylenetriaminepropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

22. Molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin prepared by the method according to any one of claims 1 to 21.

23. Use of the molybdenum disulfide nanosheet modified urea-formaldehyde / melamine resin according to claim 22 in oil field sand control.

Citation Information

Patent Citations

  • Preparation method of organic modified molybdenum disulfide nanosheets

    CN105646944A

  • Hollow molybdenum disulfide-polyaniline "sea urchin"-shaped composite material and preparation method thereof

    CN109449001A

  • Modified MoS2 nano material and preparation method thereof

    CN109943310A

  • Preparation method of melamine modified urea formaldehyde fibers

    CN110359120A

  • Nano drag reducer, preparation method thereof and slickwater fracturing fluid

    CN113004472A

Cited By

  • Polymer foam with high photothermal conversion efficiency and preparation method thereof

    CN120944290A